Kendrick-Brooks family papers - Brooks, Charlotte, 1918-1998.; Kendrick, Hattie, 1894-1989.; Kendrick, Ruby Moyse, 1886-1986.; Mitchell, Antoinette Brooks, 1892-1972.; Mitchell, Louis A., 1885-1957.; Mitchell, Louis A., 1914-1972.
Correspondence, book drafts, transcripts of audiotapes, family papers, genealogical charts and research, business records, scrapbooks, printed material, photographs, and other papers pertaining to members of the Brooks and Kendrick families.
Ruby Moyse Kendrick's papers document her participation in the National Association of Colored Women's Clubs, her work as an educator and her social life in Greenville, Miss., and her husband Swan M. Kendrick's position with the National Association for the Advancement of Colored People (NAACP), Washington, D.C. Other family members represented include Martha Cobb and Webster M. Kendrick. Topics include race riots, African Americans in the press, lynching, and race and manpower in the U.S. Army during World War I. Correspondents include R.P. Andrews, Ray Stannard Baker, Samuel G. Blythe, Edward W. Brydie, Hervey A. Clemons, Octavus Roy Cohen, Irene M. Gaines, Rosa Lee Slade Gragg, Charles A. Howard, F.D. Johnson, T.S. Littlejohn, Ruby Elizabeth Stutts Lyells, Mabel Neely, Addie Pickle, Mamie B. Reese, Harrison Rhodes, and A.M. Trawick.
Papers of Hattie Kendrick consist chiefly of transcripts of audiotape recordings concerning Kendrick family history and the life of the cotton farming family in Bolivar County, Miss., around 1900. Other topics include Hattie's life and work as an educator in Cairo, Ill., her involvement in civil rights and social activism, and African Americans in education.
Antoinette Brooks Mitchell papers consist of scrapbooks containing correspondence, contracts, programs, newspaper clippings, photographs, and other papers documenting Louis A. Mitchell's career as a musician, band leader, restaurateur, and nightclub owner in the U.S., England, and France during the first half of the twentieth century, his role in the introduction of jazz to Europe, and his participation in baseball leagues in England and France, 1917-1918. Also includes papers of their son Louis A. (Jack) Mitchell. Correspondents include Walter H. Brooks, Louis Bustanoby, Vernon Castle, Victor Emmanuel, Leonard F. Guttridge, Bernie Harrison, Julian Jones, and Dan Kildare.
Papers of Charlotte Brooks comprise research files used in compiling Brooks and Kendrick family histories. Family members represented include Albert R. Brooks and his wife Lucy Goode Brooks. Subjects include slavery and migration to the North.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Brooks and Kendrick family members which include club women, civil rights activists, educators, and entertainers.
Collection material in English and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Andrews, R. P. -- Correspondence; Baker, Ray Stannard, -- 1870-1946 -- Correspondence; Blythe, Samuel G. -- 1868-1947 -- Correspondence; Brooks, Albert R; Brooks, Lucy Goode; Brooks, Walter H. -- 1851- -- Correspondence; Brydie, Edward W. -- Correspondence; Bustanoby, Louis, -- -1917 -- Correspondence; Castle, Vernon, -- 1887-1918 -- Correspondence; Clemons, Hervey A. -- Correspondence; Cobb, Martha; Cohen, Octavus Roy, -- 1891- -- Correspondence; Gaines, Irene M. -- 1896-1964 -- Correspondence; Gragg, Rosa Lee Slade, -- 1904-1989 -- Correspondence; Guttridge, Leonard F. -- Correspondence; Harrison, Bernie -- Correspondence; Howard, Charles A. -- Correspondence; Johnson, F. D. -- Correspondence; Jones, Julian -- Correspondence; Kendrick, Swan M., -- 1885-1923.; Kendrick, Webster M; Kildare, Dan, -- 1879-1920 -- Correspondence; Littlejohn, T. S. -- Correspondence; Lyells, Ruby Elizabeth Stutts, -- 1908- -- Correspondence; Neely, Mabel -- Correspondence; Pickle, Addie -- Correspondence; Reese, Mamie B. -- Correspondence; Rhodes, Harrison, -- 1871-1929 -- Correspondence; Trawick, A. M. -- 1869- -- Correspondence; Brooks family; Kendrick family; United States. -- Army -- African American troops; National Association for the Advancement of Colored People; National Association of Colored Women's Clubs (U.S.); African American musicians -- Europe; African American musicians; African Americans -- Education; African Americans -- Societies, etc; Baseball -- England; Baseball -- France; Civil rights -- United States; Cotton growing -- Mississippi -- Bolivar County; Education -- Illinois -- Cairo; Education -- Mississippi -- Greenville; Jazz -- Europe; Lynching; Migration, Internal -- United States; Nightclubs -- England; Nightclubs -- France; Nightclubs -- United States; Press -- United States; Restaurateurs -- England; Restaurateurs -- France; Restaurateurs -- United States; Riots -- United States; Slavery -- United States; Social problems -- United States; World War, 1914-1918 -- African Americans; World War, 1914-1918 -- Manpower; Bolivar County (Miss.) -- History